Acid-catalyzed rearrangements in arenes: interconversions in the quaterphenyl series - Skraba-Joiner, Sarah L.; Holt, Carter J.; Johnson, Richard P. (Beilstein Journal of Organic Chemistry, 2019)
Arenes undergo rearrangement of phenyl, alkyl, halogen and other groups through the intermediacy of ipso arenium ions in which a proton is attached at the same carbon as the migrating substituent. Interconversions among the six quaterphenyl isomers have been studied here as a model for rearrangements of linear polyphenyls. All reactions were carried out in 1 M CF3SO3H (TfOH) in dichloroethane at 150 °C in a microwave reactor for 30–60 min, with product formation assessed by high field NMR analysis. Under these reaction conditions, m,p'-quaterphenyl is the equilibrium product. This isomer is unchanged by the reaction conditions and all other quaterphenyl isomers rearrange to m,p' as the dominant or sole product. DFT computations with inclusion of implicit solvation support a complex network of phenyl and biphenyl shifts, with barriers to rearrangement in the range of 10–21 kcal/mol. Consistent with experiments, the lowest energy arenium ion located on this surface is due to protonation of m,p'-quaterphenyl. This supports thermodynamic control based on carbocation energies.
Keywords: arenium ion; carbocation; density functional theory; microwave reaction; rearrangement; superacid